REVIEW OF GLOBAL 2.1-1.8 GA OROGENS: IMPLICATIONS FOR A PRE-RODINIA SUPERCONTINENT - Zhao G.; Sun M.; Cawood P.A.; Wilde S.A. (My University, 2002)
Available lithostratigraphic, tectonothermal, geochronological and paleomagnetic data from 2.1–1.8 Ga collisional orogens and related cratonic blocks around the world have established connections between South America and West Africa; Western Australia and South Africa; Laurentia and Baltica; Siberia and Laurentia; Laurentia and Central Australia; East Antarctica and Laurentia, and North China and India. These links are interpreted to indicate the presence of a supercontinent existing before Rodinia, referred to herein as Columbia, a name recently proposed by Rogers and Santosh [Gondwana Res. 5 (2002) 5] for a Paleo-Mesoproterozoic supercontinent. In this supercontinent, the Archean to Paleoproterozoic cratonic blocks were welded by the global 2.1–1.8 Ga collisional belts. The cratonic blocks in South America and West Africa were welded by the 2.1–2.0 Ga Transamazonian and Eburnean Orogens; the Kaapvaal and Zimbabwe Cratons in southern Africa were collided along the ∼2.0 Ga Limpopo Belt; the cratonic blocks of Laurentia were sutured along the 1.9–1.8 Ga Trans-Hudson, Penokean, Taltson–Thelon, Wopmay, Ungava, Torngat and Nagssugtoqidian Orogens; the Kola, Karelia, Volgo–Uralia and Sarmatia (Ukrainian) Cratons in Baltica (Eastern Europe) were joined by the 1.9–1.8 Ga Kola–Karelia, Svecofennian, Volhyn–Central Russian and Pachelma Orogens; the Anabar and Aldan Cratons in Siberia were connected by the 1.9–1.8 Ga Akitkan and Central Aldan Orogens; the East Antarctica and an unknown continental block were joined by the Transantarctic Mountains Orogen; the South and North Indian Blocks were amalgamated along the Central Indian Tectonic Zone; and the Eastern and Western Blocks of the North China Craton were welded together by the ~1.85 Ga Trans-North China Orogen.